LinkAge - Jubany, Olga (Col·lecció Biblioteca Universitària, 2013)
The current intersection of long-term economic restructuring and demographic adjustments across Europe has produced major patterns of inequality in the labour market, with a distinctly uneven impact depending on the age of workers. The dismissal of older workers and the blockage of occupational integration of youngsters have led to a dramatic decline of labour market participation at both ends of the age spectrum; a context in which trade unions have become a vital inclusive instrument. LinkAge analyses the extent to which social dialogue represents the interests of younger and older workers in a mapping of six European countries, addressing challenging questions such as: What is the impact of welfare retrenchment policies for these workers? Is a zero-sum approach applied as a cost-distribution strategy? and What are unions' approaches to tackle age discrimination? Relying on the ethnographic insights from workers, experts, trade unions and employers' representatives, the research explores the effects of demographic and intergenerational dynamics on the working population, and society as a whole.